Maps apps, street level imagery live as traffic information: the possible role of creative online communities - Neves , Pedro Soares (Architecture Image Studies, 2021)
Map applications use very distinct times for updating satellite, traffic information or street level imagery. Street level imagery is the less updated and traffic information is updated continuously. Having as departure point the analysis of traffic data consistency facing reality (using as case study a group of streets in Lisbon). This article explores the traffic information updating processes and places them in relation with the state of the art street level imagery renovation efforts. References, about traffic sources of information and crowd sourcing street level imagery, will be analysed and placed in relation with the potential role of crowd sourcing trough specific creative communities.